2001
DOI: 10.1590/s0100-736x2001000400004
|View full text |Cite
|
Sign up to set email alerts
|

Natural infection of calves by Anaplasma marginale in dairy herds of the Metalúrgica Region, Minas Gerais

Abstract: Os animais que nasceram no período de março a julho sofreram a infecção em outubro e novembro, independentemente da idade, enquanto os que nasceram no período de setembro a dezembro adquiriram a infecção nos primeiros dias de vida, com parasitemia patente a partir de 30 dias de idade. Durante o período patente, o VG reduziu na primeira semana de infecção, variando entre 20 a 23%. Concluiu-se que a ocorrência da primo-infecção sofre influência das estações do ano e que bezerros nascidos na estação seca apresent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…microplus (ARTILES et al, 1995;DALAGNOL;MADRUGA, 1995). Neste estudo, a maior frequência de bezerras soropositivas para A. marginale, tanto para propriedades produtoras de LB ou LCR, está relacionada à resistência inata de bovinos jovens ao protozoário B. bovis (GOFF et al, 2010), fato não observado em relação à A. marginale; aliado a competência de vetores biológicos e mecânicos em transmitir está riquétsia (SCOLES et al, 2005) (MADRUGA et al, 1985;PEDREIRA;ALMEIDA, 1992;ARAÚJO et al, 1998;MELO et al, 2001).…”
Section: Discussionunclassified
“…microplus (ARTILES et al, 1995;DALAGNOL;MADRUGA, 1995). Neste estudo, a maior frequência de bezerras soropositivas para A. marginale, tanto para propriedades produtoras de LB ou LCR, está relacionada à resistência inata de bovinos jovens ao protozoário B. bovis (GOFF et al, 2010), fato não observado em relação à A. marginale; aliado a competência de vetores biológicos e mecânicos em transmitir está riquétsia (SCOLES et al, 2005) (MADRUGA et al, 1985;PEDREIRA;ALMEIDA, 1992;ARAÚJO et al, 1998;MELO et al, 2001).…”
Section: Discussionunclassified
“…In Brazil, the former agents are transmitted by Rhipicephalus (Boophilus) microplus, while the latter one, besides biological transmission by tick, can also be mechanically transmitted by hematophagous diptera (GUGLIELMONE, 1995). Epidemiological studies showed that, in Brazil, B. bovis, B. bigemina and A. marginale are endemic in several areas (ARA-ÚJO et al, 1998;SMITH et al, 2000;SOARES et al, 2000;SOUZA et al, 2000;MELO et al, 2001;ARAÚJO et al, 2005;BARROS et al, 2005, D'ANDREA et al, 2006. Other factor that may influence the distribution of these pathogens is breed, as B. indicus cattle, because of tick resistance, are less likely to be infected by ticks.…”
Section: Introductionmentioning
confidence: 99%
“…These pests of cattle cause notable economic losses and several studies have attempted to estimate their economic impact on cattle production (Catangui et al, 1997). They represent a serious nuisance not only because of their painful bites and the blood predation, but they can also be vector of pathogens (Zumpt, 1973;Foil et al, 1983;Skidmore, 1985;Freitas & Romero, 1991;D'Amico et al, 1996;Melo et al, 2001;Foil & Gorham, 2003). No study on the dynamics of Stomoxyine populations has been conducted in Thailand, eventhough they are suspected there to be an important vector of animal trypanosomoses by the local authorities.…”
mentioning
confidence: 99%